Dirt layers and atmospheric transportation of volcanic glass in the bare ice areas near the Yamato Mountains in Queen Maud Land and the Allan Hills in Victoria Land, Antarctica - Nishio, Fumihiko; Katsushima, Takayoshi; Ohmae, Hirokazu; Ishikawa, Masao; Takahashi, Shuhei (1984)
P(論文) Dirt layers containing volcanic ash fragments were found on the bare ice surface in the Meteorite Ice Field near the Yamato Mountains, Queen Maud Land, and near the Allan Hills, Victoria Land. The grain size analysis of volcanic ash fragments shows that the mean grain size in the Allan Hills region is larger than that in the Yamato Mountains region. This fact indicates that the volcanic sources of the dirt layer in the Yamato Mountains region is farther away than that for the Allan Hills. Based upon the equations describing the transport of volcanic ash fragments, the distance of atmospheric transportation can be predicted by the grain size distribution, and, furthermore, the tephra sources are estimated. The age of ice-containing tephra is also discussed. departmental bulletin paper